1997
DOI: 10.1002/art.1780401220
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association of hla‐drb1 genotype with radiologic progression in japanese patients with early rheumatoid arthritis

Abstract: Objective. To evaluate the role of HLA-DRB1 genotypes in the development and progression of the rheumatoid arthritis (RA) disease process.Methods. Patients with polyarthritis of <1 year in duration were consecutively enrolled in the study. Other inclusion criteria were no diagnosis of inflammatory diseases other than RA, and no history of taking disease-modifying antirheumatic drugs or steroids. Patients were evaluated every 4 weeks, and radiographs of the handstwrists and feet were taken at presentation and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 21 publications
2
13
1
Order By: Relevance
“…On the other hand, ValenzuelaCastano et al [20] reported no relationship between SE and the severity of structural joint damage in large joints. In 1997, we demonstrated that SE alleles failed to correlate with more severe disease [7]. In our current study, we used 123 of these 198 patients, showing a contradiction in the results.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…On the other hand, ValenzuelaCastano et al [20] reported no relationship between SE and the severity of structural joint damage in large joints. In 1997, we demonstrated that SE alleles failed to correlate with more severe disease [7]. In our current study, we used 123 of these 198 patients, showing a contradiction in the results.…”
Section: Discussioncontrasting
confidence: 69%
“…The patients were derived from those reported in our previous study [7]; thus, they visited our outpatient clinic at the Institute of Rheumatology, Tokyo Women's Medical University, within 1 year of symptom onset and were enrolled in a prospective follow-up study between 1991 and 1995. For this study, we used 123 of 198 patients, who satisfied the American College of Rheumatology (ACR) 1987 criteria for RA [8].…”
Section: Methodsmentioning
confidence: 99%
“…Although the shared epitope hypothesis was initially proposed to explain genetic susceptibility to RA, subsequent investigations have suggested that the primary role of the shared epitope may be involved in the development of more severe manifestations. Numerous studies have pursued clarification of this relationship, but so far, no consensus has been reached (Weyand et al 1992;Vehe et al 1994;Benazet et al 1995;Higami et al 1997;Kim et al 1997;Wassmuth and Wagner 2002;Del Rincon et al 2003;Gorman et al 2004;Goronzy et al 2004). These inconclusive results may be related to ethnic and clinical heterogeneity between patient populations.…”
Section: Discussionmentioning
confidence: 92%
“…There has also been the suggestion that there is a hierarchy of risk associated with various SE alleles and allele combinations, with DR␤1*0401 carrying the highest risk of destructive disease (9,21). Interestingly, SE was not associated with erosions in a Japanese cohort of early RA patients, although the prevalence of DR␤1*0401 in this population was low (22). We therefore attempted to clarify whether SE alleles, either alone or in combination with other HLA alleles, were a risk factor for the development of early erosions in our cohort.…”
Section: Discussionmentioning
confidence: 99%